USE OF DIFFERENT NARRATIVES TECHNIQUES BY RK NARAYAN - Kaur , Komalpreet (International Journal of Psychosocial Rehabilitation, 2020)
The story system is an indivisible piece of the book. Narayan involved different story procedures in his fiction. Narayan composes in regards to social issues and issues of south Indian particularly customary occupants in his books and stories. Narayan has taken up genial issues of regular daily existence; and he has tried to handle the issues through the comprehension of characters. Narayan is considered as a 'conceived narrator' or 'a top notch narrator'. The wide assortment of topics in Narayan's accounts is resembled by a comparably fulfilling assortment of procedures. Narayan has utilized a twofold story strategies, he utilizes the account methods with reason. He utilizes streak back account procedure. This makes Raju measure his own character. In this portrayal of past presence, Raju shows sufficient legitimacy and truthfulness. He depicts himself with extraordinary strength. The Guide is one of Narayan's most fascinating and well known works and is told in a progression of flashbacks. In this astute Raju is the storyteller of his past and calls attention to his perspectives from memory. Through streak dark, Raju occur with the account of his past. The laying of the railroad track at last finishes and a rail route station is fanned out at Malgudi. The memory of Raju makes the first more sensible. The flashback system excites the interest and the interest of the peruser. It moreover demonstrates Narayan's expertise as a conceived narrator. Narayan utilizes the fascinating methodology of a shifted account viewpoint. The story shifts this way and that among first and third individual account; sometimes it is Raju, the essential person talking, and at different times the story is told by the viewpoint of a vastly proficient storyteller. The creator similarly uses consistent with life parts and flashback procedures.